False aneurysms of the Renal Artery: is it a known diagnosis in the medical community? - Machado,Marta (2020)
Abstract Introduction: False aneurysms of the Renal Artery usually originate from iatrogenic causes or renal trauma. The incidence is increasing because minimally invasive procedures have become widely used in the treatment of renal pathology and therefore iatrogenic injuries have become more frequent. Due to the nature of the wall, they have a high risk of rupture and should therefore be diagnosed and treated soon. Objective: To evaluate the experience of the CHUP’s angiology and vascular surgery department in the approach of false aneurysms of the renal artery from 2010 to 2018. Methods and Material: A retrospective review was undertaken using the clinical and imagiological records of 20 patients diagnosed with FRA. Results: Etiology was iatrogenic in 95% of the cases. All patients were symptomatic and 85% had macroscopic hematuria. The time between injury and clinical manifestation was 4.5 days. The therapy performed in all cases consisted of embolization of the FRA feeding artery. The time between injury and treatment was 18.1 days. The kidney salvage rate was 95%. Discussion/Conclusion: In this study, the main etiology and the surgical technique used are in agreement with the published literature. With this kidney salvage rate we can conclude that endovascular treatment is an effective method of treatment of these lesions. Although there are no published references in the literature, we observed that the time between injury and treatment was high, which translates into a late diagnosis. Therefore, the urologists' awareness of this complication is extremely important.